2017
DOI: 10.13005/ojc/330527
|View full text |Cite
|
Sign up to set email alerts
|

Templated Roughness on the Surface of Polyamide Nanofibrous Mat by Mesh Electrospinning

Abstract: In this study, it was aimed to present a nanofibrous scaffold with intentional roughness through a new electrospinning method called "mesh electrospinning method". Firstly, polyamide nylon 6 granules were dissolved in formic acid in different concentration (10-35 %w/v). A mesh template was placed between tip and collector in different distance (4 positions) in a conventional electrospinning line. The number of mesh layers and effects of processing parameters also considered. As it was expected, the results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“… 60 M. Saadatmand et al prepared different templates for the non-conducting polymer with a pentagon and tetragon geometry. 61 When cetirizine (anti-histamine drug)-loaded PCL nanofibres were deposited on these non-conducting templates, patterned cavities with random deposition were formed. The transdermal drug-release studies demonstrated a burst and immediate release profile, since the spacing between the pattern was more, i.e.…”
Section: Drug-encapsulation and Controlled-release Strategiesmentioning
confidence: 99%
“… 60 M. Saadatmand et al prepared different templates for the non-conducting polymer with a pentagon and tetragon geometry. 61 When cetirizine (anti-histamine drug)-loaded PCL nanofibres were deposited on these non-conducting templates, patterned cavities with random deposition were formed. The transdermal drug-release studies demonstrated a burst and immediate release profile, since the spacing between the pattern was more, i.e.…”
Section: Drug-encapsulation and Controlled-release Strategiesmentioning
confidence: 99%
“…cilostazol is Variant techniques have been employed to enhance cilostazol solubility and bioavailability including spray drying, supercritical fluid techniques (Kim et al, 2005) complexation with cyclodextrins sulfonate and mesylate salts of cilostazol (Bae et al, 2015), However these techniques decreased the particle size only to micro range and did not exhibit sustained release pattern. Electrospinning is a potential technique which is implemented to produce nano scaled fibers for drug delivery [Saadatmand et al, 2019]. The nanometer-scaled fibers exhibit high surface-to mass ratio [Sasmal et al, 2019]and high porosity [Liao et al, 2015] which gives rise to floating behavior in addition to enhancing drug solubility.…”
Section: Introductionmentioning
confidence: 99%